2012
DOI: 10.1002/hep.24699
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor c-Jun Protects Against Sustained Hepatic Endoplasmic Reticulum Stress Thereby Promoting Hepatocyte Survival

Abstract: Endoplasmic reticulum (ER) stress due to accumulation of hepatoviral or misfolded proteins is increasingly recognized as an important step in the pathogenesis of inflammatory, toxic, and metabolic liver diseases. ER stress results in the activation of several intracellular signaling pathways including Jun N‐terminal kinase (JNK). The AP‐1 (activating protein 1) transcription factor c‐Jun is a prototypic JNK target and important regulator of hepatocyte survival, proliferation, and liver tumorigenesis. Because t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
61
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 39 publications
7
61
0
Order By: Relevance
“…Current evidence suggests that JNK activation may promote cellular injury and apoptosis, but others have found that its induction may be a mechanism of cellular adaptive response to chronic stresses. 34 Given the role of IRE1a in preventing ER stress-induced hepatic steatosis, the suppression of JNK may reflect its role in nonapoptotic stress signaling responses in the development of hepatic injury secondary to iron, ethanol, and obesity. 35 To strengthen the argument for the role of iron in ER stress, we also examined pathways that are related to the UPR.…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence suggests that JNK activation may promote cellular injury and apoptosis, but others have found that its induction may be a mechanism of cellular adaptive response to chronic stresses. 34 Given the role of IRE1a in preventing ER stress-induced hepatic steatosis, the suppression of JNK may reflect its role in nonapoptotic stress signaling responses in the development of hepatic injury secondary to iron, ethanol, and obesity. 35 To strengthen the argument for the role of iron in ER stress, we also examined pathways that are related to the UPR.…”
Section: Discussionmentioning
confidence: 99%
“…HBV replication and expression of hepatoviral proteins such as HBx strongly activate c-Jun. 3,[8][9][10] c-Jun is a member of the dimeric activator protein 1 (AP-1) transcription factor family, which mainly consists of Jun (c-Jun, JunB and JunD) and Fos proteins (cFos, FosB, Fra-1 and Fra-2). 11 c-Jun is expressed as an immediate early gene in response to a variety of stress stimuli, growth factors and subsequent signaling through MAP kinase pathways.…”
mentioning
confidence: 99%
“…11 c-Jun is expressed as an immediate early gene in response to a variety of stress stimuli, growth factors and subsequent signaling through MAP kinase pathways. It is a major determinant of cell fate in the liver and regulates hepatocyte survival during acute hepatitis and ER stress 8,12 as well as hepatocyte proliferation following 2/3 partial hepatectomy. 13 Moreover, c-Jun acts as an oncogene in the liver and strongly promotes liver tumorigenesis in models of chemically induced HCC.…”
mentioning
confidence: 99%
“…It is a major determinant of cell fate in the liver and regulates hepatocyte survival during acute hepatitis and ER stress 8,12 as well as hepatocyte proliferation following 2/3 partial hepatectomy. 13 Moreover, c-Jun acts as an oncogene in the liver and strongly promotes liver tumorigenesis in models of chemically induced HCC.…”
mentioning
confidence: 99%
“…HBV replication and expression of hepatoviral proteins such as HBx strongly activate c-Jun. 3,[8][9][10] c-Jun is a member of the dimeric activator protein 1 (AP-1) transcription factor family, which mainly consists of Jun (c-Jun, JunB and JunD) and Fos proteins (cFos, FosB, Fra-1 and Fra-2).…”
mentioning
confidence: 99%